Neuro-Immune Modulation Effects of Sacral Nerve Stimulation for Visceral Hypersensitivity in Rats - Jin, Xue; Gharibani, Payam; Yin, Jieyun; Chen, Jiande D. Z. (Frontiers in Neuroscience, 2021)
Background: Visceral hypersensitivity (VH) is one of the underlying pathophysiologies of irritable bowel syndrome. Mast cell overactivation has been found to be one of the main causes of VH. We investigated the effects and mechanisms of actions of sacral nerve stimulation (SNS) on visceral pain in a rodent model of VH. Methods: The VH was established by an intrarectal infusion of acetic-acid (AA) in 10-day-old pups. Rats were chronically implanted with electrodes for SNS and recording electromyogram (EMG) and electrocardiogram. The acute study was performed in 2-randomized sessions with SNS (14Hz, 330μs, 40% motor threshold or MT, 30min) or sham-SNS. Later on, rats were randomized into SNS/sham-SNS groups and a chronic study was performed with 2h-daily SNS or sham-SNS for 21 days. Visceromotor reflexes were assessed by abdominal EMG and withdrawal reflex (AWR). Colon tissues were collected to study colonic acetylcholine (ACh), the enteric neurons (ChAT, nNOS, PGP9.5), mast cells activity (Tryptase, PGE2, COX2) and pain markers (NGF and Sub-P). Key Results: SNS significantly improved visceromotor reflexes assessed by the EMG and AWR, compared with sham-SNS. SNS normalized the protein expressions of ChAT and nNOS and regulated mast cells activity by downregulating Tryptase, COX2 and PGE2. Neonatal AA administration upregulated NGF and Sub-P; chronic SNS significantly decreased these pain biomarkers. Concurrently, chronic SNS increased ACh in colon tissues and vagal efferent activity. Conclusions: SNS reduces VH in rats and this ameliorating effect might be attributed to the suppression of mast cell overactivation in the colon tissue via the modulation of autonomic nervous system functions.